Impression management and CEO letters: evidence from the Portuguese banking sector - Oliveira, J.; Stéphanie Pinheiro; Azevedo, G.; Alves, S.O. (4th Symposium on Ethics and Social Responsibility Research, 2017)
This study assesses the influence of performance in the adoption of impression management strategies in the CEO letters of the Portuguese financial companies. It also evaluates the impact of financial crisis on impression management strategies. The goal is to verify whether or not there is indeed an impact on the handling of the information contained in the 128 letters included in the management report, in order to manipulate the stakeholders’ perception on the level of organizational performance. To this end, and using the content analysis of the CEO letters included in the individual annual reports of 27 financial institutions in the years 2006 to 2012 we concluded that even throughout the a financial crisis period, Portuguese finance companies do not tend to adopt more impression management strategies. , However, we have seen that in some years there existed some evidence of IM.